A potential well model for host-guest chemistry in double-network hydrogels toward mechanochemical coupling and toughening. (9th February 2023) - Xing, Ziyu; Lu, Haibao; Lau, Denvid; Fu, Yong-Qing
Abstract: Different from conventional single-network hydrogels, double-network (DN) hydrogels have attracted great research interest due to their ultra-high toughness; however, the working principles behind their complex mechanochemical coupling have not been fully understood. In this study, an extended potential well model is formulated to investigate the host-guest chemistry and the free-energy trap effect, coupled in DN hydrogels undergoing mechanochemical toughening. According to the Morse potential and mean field model, the newly established potential well model can describe the coupled binding of the host brittle network and guest ductile network in the DN hydrogels. A free-energy equation is further proposed to describe the working principles of the mechanochemical coupling and toughening mechanisms using the depth, width, and trap number of potential wells, which determine the barrier energy of the host brittle network, the mesh size of guest ductile network, and the mechanochemical host-guest interactions of these two networks, respectively. Finally, the effectiveness of the proposed model is verified using finite-element analysis (FEA) and experimental results of various DN hydrogels reported in the literature. Using the potential well model, which has host-guest chemistry from both brittle and ductile networks, this study clarifies the linking of mechanochemical coupling and toughening mechanisms in DN hyrdogels.